Hemodynamic Functional Changes in Miners - A. R. Vartanyan; G. V. Kondranin; A. V. Budayev; D. V. Vyalov; Yu. A Churlyaev (Общая реаниматология, 2006)
The paper deals with the study of hemodynamic features in miner in relation to the length of service. For this, 391 miners aged 20 to 60 years who had been working underground for 1 to 40 years were examined. Hemodynamics was studied by a non-invasive technique. The time course of changes in the basic functional parameters of the blood circulatory system and in the sympathetic activity index was estimated. The study has revealed that hemo-dynamic functional shifts in miners undergo significant changes even in young miners having a length of underground service of less than 10 years. The revealed hemodynamic changes suggest that there are two types of adaptation of the cardiovascular system to tiring physical work under high dust and gas concentrations due to underground openings. There is a cardiac type of adaptation that develops in miners having a length of underground service of less than 10 years and a vascular type that develops of adaptation in those having the length of 20 years or more. In critical conditions (severe skeletal injury or acute blood loss), adaptation disruption is most probable due to diminished precardiac loads. Not only functional, but also morphological changes in the circulatory system occur in the vascular type of adaptation due to its least physiological capacities.